Friday
March 24, 2017

Post a New Question

Posted by on Monday, October 3, 2011 at 11:30pm.

How do I solve this problem?

7(q + 2) + 3(2q -1) = -2

  • math - , Tuesday, October 4, 2011 at 10:56am

    get rid of the parentheses:

    7q + 14 + 6q - 3 = -2

    Collect all the q's on the left, and all the numbers on the right:

    13q = -13

    divide by 13

    q = -1

    Check your answer

    7(-1+2) + 3(2(-1)-1) = 7*1 + 3(-3) = 7 - 9 = -2

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question